2020
DOI: 10.3390/jcm9010276
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Circulating MicroRNAs in the Risk Stratification of Bicuspid Aortopathy

Abstract: Objective: Aortic size-based criteria are of limited value in the prediction of aortic events, while most aortic events occur in patients with proximal aortic diameters < 50 mm. Serological biomarkers and especially circulating microRNAs (miRNAs) have been proposed as an elegant tool to improve risk stratification in patients with different aortopathies. Therefore, we aimed to evaluate the levels of circulating miRNAs in a surgical cohort of patients presenting with bicuspid aortic valve disease and distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…There is a growing interest to use circulating biomarkers for risk stratification in patients with CHD such as bicuspid aortic valve. The following biomarkers are being focused on: matrix metalloproteinases (MMPs), transforming growth factor β (TGF-β), tissue inhibitors of matrix metalloproteinases (TIMPs), alpha1antitrypsin, as well as non-coding microRNAs (47,48). Cluster III represented biomarkers in secondary injury after cardiopulmonary bypass in children with CHD, such as Neutrophil gelatinase-associated lipocalin (NGAL) and SB100 protein, which mainly involved the prediction and evaluation of kidney injury and brain injury after extracorporeal circulation (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest to use circulating biomarkers for risk stratification in patients with CHD such as bicuspid aortic valve. The following biomarkers are being focused on: matrix metalloproteinases (MMPs), transforming growth factor β (TGF-β), tissue inhibitors of matrix metalloproteinases (TIMPs), alpha1antitrypsin, as well as non-coding microRNAs (47,48). Cluster III represented biomarkers in secondary injury after cardiopulmonary bypass in children with CHD, such as Neutrophil gelatinase-associated lipocalin (NGAL) and SB100 protein, which mainly involved the prediction and evaluation of kidney injury and brain injury after extracorporeal circulation (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…In former series, we showed the correlation between aortic miRs and matrix metalloproteinases (MMP)/tissue inhibitors of matrix metalloproteinases (TIMP) [12] and between peripheral whole blood miRs and aortic diameter [10]. Wu et al [13] performed a paired comparison of the miR expression between severely dilated vs. normal appearing, less-dilated aortic samples.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral whole blood for miRs analysis was sampled just before the surgery (i.e., during anesthesia induction). The expression of 10 miRs was analyzed in the intraoperatively obtained aortic tissue and peripheral whole blood (miR-1, miR-17, miR-18a, miR-19a, miR-20a, miR-21, miR-106a, miR-133a, miR-143 and miR-145), all published previously in association with aortopathies [3,10]. Primary study endpoint was the correlation between the miRs in the aortic tissue and the peripheral whole blood.…”
Section: Methodsmentioning
confidence: 99%
“…By A. Gallo et al, miR-15b was found to be an independent predictor of aortic dilatation, and the circulating level of miR-34a was negatively correlated with aortic wall elasticity in patients with BAV [ 59 ]. Lately a significant negative linear correlation was found between circulating miR-17, miR-20a, miR-106a and proximal aortic diameter [ 60 ].…”
Section: Mirnas As Biomarkers For Bav-related Taamentioning
confidence: 99%